If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(4x + -5) + 5(5x + -3) + -6 = 2 + -4 Reorder the terms: -6(-5 + 4x) + 5(5x + -3) + -6 = 2 + -4 (-5 * -6 + 4x * -6) + 5(5x + -3) + -6 = 2 + -4 (30 + -24x) + 5(5x + -3) + -6 = 2 + -4 Reorder the terms: 30 + -24x + 5(-3 + 5x) + -6 = 2 + -4 30 + -24x + (-3 * 5 + 5x * 5) + -6 = 2 + -4 30 + -24x + (-15 + 25x) + -6 = 2 + -4 Reorder the terms: 30 + -15 + -6 + -24x + 25x = 2 + -4 Combine like terms: 30 + -15 = 15 15 + -6 + -24x + 25x = 2 + -4 Combine like terms: 15 + -6 = 9 9 + -24x + 25x = 2 + -4 Combine like terms: -24x + 25x = 1x 9 + 1x = 2 + -4 Combine like terms: 2 + -4 = -2 9 + 1x = -2 Solving 9 + 1x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 1x = -2 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = -2 + -9 1x = -2 + -9 Combine like terms: -2 + -9 = -11 1x = -11 Divide each side by '1'. x = -11 Simplifying x = -11
| -3(4x+2)= | | 86-76=39y-44y | | 4w^2+4w+1= | | -4.22-0.807= | | 3x^(1/2)-7x^(1/4)=6 | | -4*10= | | 32x+24y=640 | | 20n+12=16n-16 | | 8x-7=8(x+2) | | 10y-120+3x+45=180 | | 9/5(-10)+32=f | | X+14/13=12/13x | | x+3/12=5/6 | | 9x-(4x-9)=7+4x | | (2x-7)=7 | | 6-8y=5y+19 | | 3t+6t=16-8+28 | | 8(11v)= | | 3^3/2-6=75 | | 40x^2-83x+42=0 | | -25=m-8 | | 3*2-1/5*4+23 | | 2b-5-11b-7= | | 3t+6t=18-8+28 | | 17-1/5(35n+15)=-8n-15 | | ((2*a^-5*b^4*c^3)^-2)/((3*a^3*b^-7*c^3)^2) | | y=3.3x-6.6 | | -3/2+7 | | 45.00(15.00+x)=1935 | | 0.6x-1.7=0.70 | | C=5/9(23-32) | | 3L/5=7 |